Ultrafine TiO2 nanocrystalline anchored on nitrogen-doped amorphous mesoporous hollow carbon nanospheres as advanced anode for lithium ion batteries. (10th February 2019) - Yuan, Yongfeng; Chen, Fei; Cai, Gaocan; Yin, Simin; Zhu, Min; Wang, Lina; Yang, Jinlin; Guo, Shaoyi
Abstract: Nitrogen-doped amorphous mesoporous hollow carbon nanospheres are prepared through the unique polymerization reaction between 3-aminophenol and formaldehyde, the selective removal effect of acetone as well as a simple carbonization process. Ultrafine TiO2 nanocrystalline with average size of 7.4 nm are further uniformly, sparsely, tightly anchored onto hollow carbon nanospheres through hydrolysis deposition of titanium tetraisopropanolate followed by a controllable crystallization. As anode material for lithium ion batteries, TiO2 @hollow carbon nanospheres exhibit high charge-discharge capacity, stable cycling performance and excellent rate capability. The average discharge capacity over 200 cycles at 1C is 242 mAh g −1, 2C and 5C are 188 and 170 mAh g −1 . After rate test and subsequent 1500 continuous cycles at 10C, TiO2 @hollow carbon nanospheres still deliver discharge capacity of 146.1 mAh g −1 with a high capacity retention of 80.6% and a very low capacity decay of 0.012% per cycle. The superior lithium storage properties should be attributed to synthetic effects of ultrafine TiO2 nanocrystalline and hollow carbon nanospheres. This work can give rise to the new understanding about design and synthesis of next-generation, high-power TiO2 -based advanced anode for lithium ion batteries.